Aesthetics of Poetic Language in the Dewan of "Nawhi" (Raparin Journal of Humanities (RJH), 2023)
This research, entitled "Aesthetics of Poetic Language in the Dewan of Nawhi", is an attempt to highlight the aesthetics of poetic language in general and the aesthetics of poetic language in particular in the poems of a little-known poet of Kurdish literature It is grammatically defined in the structure of Noah's poetic language, which includes both lexical and syntactic levels. Through examples of his poetic texts, the aesthetic aspects and levels of the poet's poetic language, ability and poetic experience have been identified and presented. To conduct this research, the method (analytical description) has been used to reveal the purpose and content of poetic texts and analyze them grammatically. To achieve the goal, the research is divided into an introduction and two topics, which theoretically discusses the concept and definition of poetic language and in practice covers the structure of Noah's poetic language in terms of grammar. Finally, the results are summarized in several points.